Mulheres e funk: valores, crenças e ethos - Prada, Carla Moreira de Paula (2020)
This research is inserted in the Portuguese language area, research field text and speech, in the oral and written modalities and has as main theme the built of the woman’s ethos in the Brazilian funk, established in its own speech, as well as the discursive power that the rhythm funk incorporates from its social construction. Based on the dissent rhetoric, which designates a polarization of ideas, we mainly based ourselves in rhetorical concepts from Aristotle. (2004; 2011;2017), Meyer (2007), Amossy (2016), Ferreira (2017) and others to analyse the lyrics from the songs Dako é bom (2004), by MC Tati Quebra-Barraco and 100% feminista (2014) by MC Carol feat. Karol Comká, in order to, this way, investigate which rhetorical resources are used in the ethos’ built of the orator in these productions. The problem, therefore, is to question how the ethos is built inside funk lyrics composed by women in a space previously dominated by male speakers. In this direction, our general objective is to reflect on the power of the word in the funk music genre and its development as a mass culture, to broaden the knowledge about the ethos that emerges from contemporary female compositions. As specific objectives, we define: I) Verify how the construction of the female ethos in funk occurs rhetorically; II) Find out if there is a transformation of the female ethos throughout these productions; III) identify the rhetorical-argumentative marks for the construction of the feminine ethos; IV) Verify the discursive power of funk as a mean of cultural manifestation. In addition, we highlight throughout the analyses the use of the rhetorical system as a hermeneutic role to grasp the aspects related to the built of the feminine ethos. We also established a rhetorical comparative analysis of those lyrics to highlight the transformation of the feminine ethos over the years. Besides that, we discussed the speaking place; to do so, we based ourselves in Ribeiro’s theory (2016), to be able to demonstrate the role of the funk woman. We arrived to the conclusion that the funk contemplates the characteristics of the constituent discourse. Furthermore, the feminine ethos undergoes a transformation in the discursive process and women start to build their ethos in an independente way, yearning for social changes